2016
DOI: 10.3109/1547691x.2015.1122116
|View full text |Cite
|
Sign up to set email alerts
|

A higher aspect ratio enhanced bioaccumulation and altered immune responses due to intravenously-injected aluminum oxide nanoparticles

Abstract: Aluminum oxide nanoparticles (AlO NP) have been widely utilized in a variety of areas, including in the optical, biomedical and electronic fields and in the overall development of nanotechnologies. However, their toxicological profiles are still not fully developed. This study compared the distribution and immunotoxicity of two rod-types of AlO NP. As reported previously, the two types of AlO NP had different aspect ratios (long-type: 6.2 ± 0.6, short-type: 2.1 ± 0.4), but the size and surface charge were very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Similarly, aluminum‐induced brain damage altered the level of antioxidant elements in the brain (Solfrizzi et al, ; Tripathi et al, ), and pulmonary exposure to AlONPs induced the inflammatory response with oxidative stress (Lu et al, ). Additionally, in our previous studies, AlONPs influenced the tissue homeostasis of redox reaction‐related trace elements, including Mn, Zn, Cu and Fe (Park, Sim, et al, ; Park, Kim, et al, ; Park, Lee, et al, ). In the present study, we also found that the level of redox‐reaction‐related trace elements in tissues was altered after exposure to the three types of AlONPs.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Similarly, aluminum‐induced brain damage altered the level of antioxidant elements in the brain (Solfrizzi et al, ; Tripathi et al, ), and pulmonary exposure to AlONPs induced the inflammatory response with oxidative stress (Lu et al, ). Additionally, in our previous studies, AlONPs influenced the tissue homeostasis of redox reaction‐related trace elements, including Mn, Zn, Cu and Fe (Park, Sim, et al, ; Park, Kim, et al, ; Park, Lee, et al, ). In the present study, we also found that the level of redox‐reaction‐related trace elements in tissues was altered after exposure to the three types of AlONPs.…”
Section: Discussionmentioning
confidence: 83%
“…S‐AlONPs were well dispersed (Figure A), whereas L‐AlONPs showed an aggregated appearance (Figure B). S‐ and L‐AlONPs had anisotropic shapes with different aspect ratios (length‐to‐diameter) of 2.1 ± 0.4, and 6.2 ± 0.6, respectively (Park, Lee, et al, ; Park, Kim, et al, ). The XRD patterns obtained from both S‐ and L‐AlONPs were primarily indexed to δ phase, although S‐AlONPs were δ phase with the I space group (PDF no.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations